New Indicator for Health Monitoring of Structures Made of Fiber-Reinforced Composite Materials Under Low Impact Loading - Budiyan Mariyadi, Fergyanto.E.Gunawan, Arief S. Budiman (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Structural health monitoring (SHM) is critical for the safe design and use of many societally essential structures, such as bridges, highway infrastructures, high-density buildings, and technologically critical applications in the aerospace and automotive industries. Among the many modes of mechanical loading, dynamic loading (such as vibration or impact) is perhaps the most crucial as it often leads to sudden failure of the structures. In addition, more structures – such as aircraft, spacecraft, and even automobiles – are currently built with composite materials due to their high specific strength and toughness (compared to metals). Although many SHM studies have been performed in structures made of fiber-reinforced composites, the response of structures, especially concerning high impact loading mode, may be different compared to metals is one example of such a unique damage mechanism in composites. We propose here new damage indicator based on the theory of strength of materials applied to plate geometry. The findings suggest that the new damage indicator is more sensitive towards detecting failure of the materials or structures, compared to the existing methodology.